EFFECT OF CHOLINE AND LECITHIN ON GROWTH AND FEED EFFICIENCY OF JUVENILE HUMPBACK GROUPER, Cromileptes altivelis - Ketut Suwirya; Nyoman Adiasmara Giri (Research Center for Fisheries, 2002)
This experiment was conducted to determine the effect of supplemental choline and lecithin in the diet of juvenile humpback grouper.